Effect of Sintering Temperature on Membranes Manufactured with Clays for Textile Effluent Treatment - Mirele Costa da Silva; Hélio de Lucena Lira; Rosa do Carmo de Oliveira Lima; Normanda Lino de Freitas (Advances in Materials Science and Engineering)
The aim of this work is to use cheap raw materials, such as kaolin and ball clay, for the manufacture of ceramic membranes for application in effluent treatment from textile industry and to evaluate the influence of sintering temperature in the structural and morphological characteristics of those membranes. The ceramic mass was characterized by X-ray diffraction and thermal analysis. The membranes were characterized by scanning electron microscopy, Hg porosimetry, and water permeability with desalinated water. The variation in the sintering temperature directly affected the structural and morphological characteristics of the membranes. The increase in sintering temperature of the membranes has raised the average pores diameter from 0.116 to 0.179 µm but decreased the porosity of the membrane, from 40.30 to 25.16% for temperatures from 900 to 1100°C, respectively. The reduction in porosity of the membrane affected the water permeated flux and decrease from 35.82 Kg/h·m2 (at 1000°C) to 15.68 Kg/h·m2 (at 1100°C). All the membranes have been applied with success in the effluent treatment from textile industry, resulting in the decrease in turbidity and discoloration, reaching approximately 100% of rejection of solid particles.